2022
DOI: 10.2478/hukin-2022-0113
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Acceleration, Deceleration and Changes of Direction in Repeated Small Sided Games

Abstract: The change of direction (COD) ability is perhaps the most significant fitness component in team sport games. One of the best ways to develop COD as well as other components of the game in soccer is the regular inclusion of small sided games (SSGs) in the training process. Therefore, the aim of this research was to determine changes in physiological and kinematic variables in repeated SSGs in youth soccer players. Additionally, we investigated the relationship between selected IMA variables such as acceleration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…It makes sense for HIIT to include SSGs since the players would also improve technical and tactical elements and their decision-making processes, which are required for playing soccer ( Davids et al, 2013 ; Trecroci et al, 2020 ) Therefore, the next aim was to determine if participants would exceed the ANT and achieve PFT intensity during four-versus-four matches on a 25 m × 35 m pitch that reflect the game conditions required in the specific HIIT proposed. The parameter frequently used in coaching practice to determine the effort intensity during the game is HR ( Brandes et al, 2012 ; Aşçı, 2016 ; Konefał et al, 2023 ), which can be measured with precision and accuracy using available measurement technologies ( Beenham et al, 2017 ; Gómez-Carmona et al, 2020 ; Pop et al, 2022 ). In this study, soccer players achieved HR max values that exceeded the intensity found at the ANT five-fold during six 3-min matches, even though they did not reach such intensity at the PFT during any of the games.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It makes sense for HIIT to include SSGs since the players would also improve technical and tactical elements and their decision-making processes, which are required for playing soccer ( Davids et al, 2013 ; Trecroci et al, 2020 ) Therefore, the next aim was to determine if participants would exceed the ANT and achieve PFT intensity during four-versus-four matches on a 25 m × 35 m pitch that reflect the game conditions required in the specific HIIT proposed. The parameter frequently used in coaching practice to determine the effort intensity during the game is HR ( Brandes et al, 2012 ; Aşçı, 2016 ; Konefał et al, 2023 ), which can be measured with precision and accuracy using available measurement technologies ( Beenham et al, 2017 ; Gómez-Carmona et al, 2020 ; Pop et al, 2022 ). In this study, soccer players achieved HR max values that exceeded the intensity found at the ANT five-fold during six 3-min matches, even though they did not reach such intensity at the PFT during any of the games.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the analysis of kinematic parameters demonstrated a requirement of six consecutive games for the players to maintain their TDC, V max, and Acc levels. Nonetheless, values for V mean and Dec indicated a need to reduce the number of games to five since these parameters significantly decreased in the final game ( Konefał et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent investigation, thanks to the information obtained from an IMMU and its processing by means of a specific algorithm, it was possible to be highly precise in detecting CoDs at different angulations, compared to high-resolution video recording [19]. To the authors' knowledge, only five studies have quantified CoDs during competition using inertial sensors, namely in players of basketball [20,21], handball [22,23], and soccer [24]. From our point of view, the number of studies related to CoD monitoring is low, although it is an important aspect of performance [25].…”
Section: Introductionmentioning
confidence: 99%